THE CREATION OF THE PERMANENT COURT OF ARBITRATION: DOCTRINAL DEBATES ABOUT ITS ORIGINS - Carlos Lima, Lucas (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2023)
Created in 1899 by the Hague Peace Convention, the Permanent Court of Arbitration is an international judicial organ whose creation takes place in a field of tension between discourses that involved the international arbitration at the time and also those which assured the need for the creation of a permanent court. Established in a background of discourses that glorified international arbitration, the Court became a target of fierce criticizing concerning its structure and inability to develop the International Law through its awards. The purpose of the present work is to historically revisit the debates on the Permanent Court of Arbitration not only for a better comprehension of the moment and the jurisdictional organ itself (which, at the present day, has suffered a severe process of modernization and adaptation to the international scene), but also to know critically the juridical discourses that involve the dynamics of the international arbitration.